(5R)-5-hydroxytriptolide (LLDT-8) prevents collagen-induced arthritis through OPG/RANK/RANKL signaling in a rat model of rheumatoid arthritis - Zeng, Ji-Zhou (Exp Ther Med, 2016)
(5R)-5-hydroxytriptolide (LLDT-8) extracts from Tripterygium have anti-inflammatory, antineoplastic and immunity adjustment functions. The present study used a collagen-induced arthritis (CIA) model to evaluate whether LLDT-8 prevents collagen-induced arthritis, and investigated the signaling underlying this. Male Sprague-Dawley rats were induced to generate CIA, mimicking rheumatoid arthritis (RA). The presence of arthritis was determined using RA progression scores. The inflammatory cytokines interleukin (IL)-1β, IL-6 and nuclear factor-κB were detected using enzyme-linked immunosorbent assay kits. Induced nitric oxide synthase (iNOS) and matrix metalloprotease (MMP)-13 protein expression were measured using western blot analysis. Lastly, reverse transcription-quantitative polymerase chain reaction was used to evaluate osteoprotegerin (OPG) and receptor activator of nuclear factor κB (RANK) gene expression. LLDT-8 improved RA progression scores and reduced the incidence and severity of CIA. Furthermore, LLDT-8 administration inhibited collagen-induced inflammation and iNOS protein expression in arthritic rats. The current data indicated that MMP-13 production was suppressed and OPG/RANKL expression was increased by LLDT-8 treatment in the arthritic rat. The present results suggest that LLDT-8 attenuates CIA through OPG/RANK/RANK ligand signaling in a rat model of RA.